Let's solve the equation \( 2(x + 8) = 2x + 8 \) step by step.
Step 1: Use the Distributive Property to get 2x + 16 resulting equation.
Starting with the original equation: \[ 2(x + 8) = 2x + 8 \]
Applying the Distributive Property: \[ 2x + 16 = 2x + 8 \]
Step 2: Use the Subtraction Property of Equality to get 16 = 8 resulting equation.
Subtract \( 2x \) from both sides: \[ 2x + 16 - 2x = 2x + 8 - 2x \] This simplifies to: \[ 16 = 8 \]
Step 3: There is/are no solutions.
The statement \( 16 = 8 \) is false, indicating that there are no values of \( x \) that satisfy the original equation.
Final summary:
- Step 1: Use the Distributive Property to get 2x + 16 resulting equation.
- Step 2: Use the Subtraction Property of Equality to get 16 = 8 resulting equation.
- Step 3: There is/are no solutions.